Variability and its limits in bilingual language production. Issue 5 (3rd October 2016) - ABUTALEBI, JUBIN; CLAHSEN, HARALD
Abstract : Experimental and other empirical research on language is faced with the fact that language performance exhibits a high degree of variability at all linguistic levels. Variability is found across languages, across speech communities within one language, across individuals within one speech community and even within the same individual. Bilingual language use adds a further source of variability to this already complicated picture. On the other hand, there are aspects of language and language use that are constrained, stable, or robust and that are less (or not at all) subject to variability, for example, possible options that are not chosen in any language or kinds of error that are never produced. Several familiar ways of dealing with the variability of language use and its limits have turned out to be unsatisfactory. One approach has been to simply abstract away from variability with constructs such as the 'ideal speaker–hearer' (who – to our knowledge – nobody has met so far). Another strategy is to average across individuals, which sometimes results in arbitrary mean scores or mean activation patterns that are hard to replicate for individuals, even for those who took part in a given study. A third solution when confronted with variability in language use is to take it at face value, positing that every language, every speech community, and even every individual is different, an approach that essentially gives up on discovering any kind of generalizations. While none of these strategies appears to us to be particularly fruitful, the problem of how to deal with variability in language performance and its limits remains.